Sistem integrasi keaman dan kenyaman lift menggunakan TAG-RFID pada berbagai obyek vital - Hudzaifah Hazazi Zia Kusuma; Jatmiko Endro Suseno; Priyono Priyono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
This paper discusses the security system of lift devices and rooms that integrated with one Radio Frequency Identification (RFID) device. The RFID tags are small, wireless devices that help identify objects that can provide convenience, security and convenience for users to improve service quality base on on the Arduino Mega 2560 microcontroller. The results of control integrated system design of between elevator doors with private rooms and other facilities can be done well. In this design, the visitor management system becomes the central integrated security system because only visitors who have access can utilize various facilities in accordance with the existing code in RFID, so this result is very potential to be applied for various control vital objects for more secure system security. Keyword: RFID, Security system, Arduino, Microcontrol